(untitled) (Journal of Social Sciences Review, 2023)
This article discusses the regulations of MARPOL 73/78 for the prevention and control of pollution by garbage from ships and its implementation in various countries. MARPOL 73/78 was adopted in 1973 and is an international convention aimed at preventing and controlling pollution from ships. Annex V of the convention regulates the disposal of garbage from ships and requires ships to keep a garbage management plan on board. The article compares the participation and implementation of Annex V in different countries, including Vietnam, the United States, and Australia. The article highlights the limitations in implementing Annex V in some countries and reports of non-compliance with the regulations in others. The article also covers the steps the US has taken to enforce the restrictions, such as the Act to Prevent Pollution from Ships. The article’s overall message emphasizes the significance of effectively putting international treaties into practice to stop marine pollution and save the marine ecosystem.